A Implementasi algoritma rabin-karp dan cosine similarity untuk pendeteksi plagiarisme pada dokumen - Eric Siswanto; Yo Ceng Giap (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
In the current era the development of information technology is developing very quickly in helping many problems quickly, accurately and efficiently. Technology development also makes it easy for us to exchange and get information, especially among students to help in the making of their assignments, but this also involves students who were originally in the Utilization so that they can more easily find references but are now used as tools for duplication or plagiarism. To ask the authors to make an application that can prove the existence of plagiarism in documents intended to find out whether this document was produced through plagiarism or not. The method used is the Rabin-Karp Algorithm used to use document similarity or analyze the thesis text similarity such as substring matching, search for keywords in documents and cosine similarity methods to produce similarities in this plagiarism detection application. The application uses the php programming language, notepad ++ and xampp applications. System testing is done using the white box method by analyzing the application flow and the black box method to access all buttons on the application as well as the questionnaire to find out the opinions of users on this application. This application compares 2 documents that were inputted by the user to test the equation, if the values ​​are 50 then it will be described in the results page that results from research that can be done in the conclusions associated with applications that support plagiarism experiments